Confirmation of the power gain for solar photovoltaic systems in alpine areas and across scales - Frischholz, Y.; Schilt, U.; Sharma, V.; Kahl, A.; Strebel, S.; Anderegg, D.; Rohrer, J.; Lehning, M. (Frontiers in Energy Research, 2024)
Introduction: High Alpine regions show a great potential for solar photovoltaic electricity production in winter due to the reflective properties of snow and the larger number of sun hours compared to lower urban and peri-urban regions. In countries with a pronounced deficit in domestic electricity production such as Switzerland, utility-scale projects of Alpine-PV power plants are now flourishing. The harsh environmental conditions and the complexity of the high-Alpine topography however challenge the conventional design practices. In this context, the main question the article addresses is the representation of test-scale measurement in the performances of Alpine-PV, utility-scale power plants. Methods: This article focuses on the comparison between long term tests and the first Alpine-PV utility-scale power plant in Switzerland. Results: The results show that the main performance indicators such as the Alpine-to-Midlands final yield ratio or the winter fraction, do scale. However, absolute final yield values are consistently lower at the utility scale. Discussion: The paper discusses the possible impacts of the complex Alpine topography as constraint for the design of the larger extent of utility-scale power plants as well as the influence of scale on the snow induced losses.